The study of the species from genus Selaginella (Selaginellaceae) in forest of Peninsular Malaysia - Nurfarahain Zainal,; Haja Maideen Kader Maideen,; Shaharuddin Mohamad Ismail, (Institute of the Malay World and Civilization, Universiti Kebangsaan Malaysia, 2018)
An anatomical study was carry out on 14 taxa belonging to Selaginellaceae in an attempt to study their stipe anatomical characteristics and to provide anatomical data for the selected taxa in Selaginellaceae. Out of 29 taxa of Selaginellaceae recorded in Peninsular Malaysia, 14 taxa have been selected namely Selaginella alutacia, S. argentea, S. frondosa, S. intermedia var. intermedia, S. intermedia var. dolichocentrus, S. mayeri, S. morganii, S. ornata, S. plana, S. polita, S. roxburghii var. roxburghii, S. stipulata, S. wallichii and S. willdenowii. Method used in this study is sectioning using sliding microtome. Findings in this study have shown that Selaginellaceae species studied can be cluster into two groups, based on the stipe stellar systems, which are monostelic and tristelic groups. There are some variations exist in the cross sections of the stipes of the same species due to the presence and absence of the leaf trace. Each species is prove to have distinct stipe anatomical characteristics that can be used to differentiate species in Selaginellaceae.